FAKTOR-FAKTOR YANG MEMPENGARUHI TUMBUH KEMBANG BALITA DI WILAYAH KERJA PUSKESMAS PANCUR BATU KABUPATEN DELI SERDANG TAHUN 2019 - Risna Melina Rumahorbo (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2020)
World Health Organization (WHO) in 2018 reported that data on the prevalence of children under five with impaired growth and development was 28.7% and Indonesia was included in the third country with the highest prevalence in the Southeast Asian region. The Pancur Batu Puskesmas report in Deli Serdang Regency stated that 90 under-five children (39%) had nutritional status below the red line (BGM). The purpose of this study was to determine the factors influencing the growth and development of children under five in the area of ​​Puskesmas Pancur Batu, Deli Serdang Regency in 2019. This research was analytic observational with cross sectional design. Data analysis used chi square test with a sample of 48 toddlers in Pancur Batu Health Center in Deli Serdang Regency in 2019. The results showed that there was a relationship between nutritional status, infectious diseases, parental income, and the level of maternal knowledge with the growth of toddlers in the region The Work of the Pancur Batu Health Center in Deli Serdang Regency in 2019. From the results of the study it was suggested that Posyandu cadres could hold a counseling program for mothers who have children under five regarding the importance of nutrition improvement efforts for families especially toddlers. Mothers who have children under five are expected to actively participate in weighing activities at Posyandu so that their growth and development can be monitored every month Keywords: nutritional status, infectious diseases, toddlers